Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.elspec.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved studies of interatomic Coulombic decay

Abstract: a b s t r a c tInteratomic Coulombic decay (ICD) is a decay mechanism occurring in loosely bound matter, e.g. in systems bound by van der Waals-forces or hydrogen bonds. In many such cases the decay time is similar to the time scale of nuclear motion during the decay. As the efficiency of ICD strongly depends on the internuclear distance of the atoms or molecules involved in the decay, an overall non-trivial temporal decay behavior arises. The progress of examining the time-domain aspects of interatomic Coulom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…It is probable that in contrast to most of previous studies of correlated electron dynamics91011125152535455 the precursors for observed CED-channels are populated few picoseconds after the absorption of XUV-photons. On this time-scale the clusters are substantially expanded and resemble a strongly diluted plasma2443.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It is probable that in contrast to most of previous studies of correlated electron dynamics91011125152535455 the precursors for observed CED-channels are populated few picoseconds after the absorption of XUV-photons. On this time-scale the clusters are substantially expanded and resemble a strongly diluted plasma2443.…”
Section: Discussionmentioning
confidence: 62%
“…and since then has been subjected to extensive theoretical and experimental investigations (see e.g. refs 9, 10, 11, 12 for reviews). For instance, low-energy ICD-electrons produced upon ionization of water dimers13 and water clusters14 are considered as a source for radiation damage in biological matter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The superexchange ICD mechanism may be observed experimentally by comparing time-resolved experiments, such as in Refs. [7,32], on Ne clusters doped with an increasing number of He atoms, on the one hand, and on homogeneous Ne clusters, on the other hand. Since these experiments rely on the detection of ions, it might be preferable to use small clusters in order to avoid charge transfer processes following ICD.…”
mentioning
confidence: 99%
“…Depending on the system, ICD takes place on the femtosecond to picosecond timescales and it is generally the dominant decay pathway unless local Auger decay is operative. While this general characteristic of ICD is well established [7], computing accurately the lifetime of the excited species, or turning from time to energy domain, the energy width of the corresponding state, remains challenging. Several methods have been implemented to compute ab initio ICD widths of ionized and/or excited atoms and molecules in small clusters.…”
Section: Introductionmentioning
confidence: 99%